Aliwalas improving passive environmental comfort in low-rise residential buildings using performance sketching - Estacio, Renee Aurora Ysobel W.
Designing for passive environmental comfort is a key strategy in creating autonomous buildings that can withstand energy precarity in the current climate crisis. However, the assessment of building comfort performance is often neglected during the design stage, which is when decisions have the most impact on passive design. Similar to how an architectural sketch is a preliminary representation of the spatial program in the schematic design phase, a performance sketch is a rough model that can predict how the building might perform. This research project delves into the use of performance sketching as a tool to guide passive strategic decisions, with the aim of enhancing environmental comfort in the design of low-rise residential buildings in east Escopa IV.